Public Education and National Security - Nazelskis, Eugenijus (Acta Paedagogica Vilnensia, 2001)
The article focuses on relation between public education and national security, also it analyse their mutual connections and review the role of public education in the context of national security. The concept of national security is not strictly defined in the law of national security of Lithuanian republic. It is a reason why relation between public education and national security became complicated, altogether the concept of security became an object of various interpretations. This article looks for reasons why there is a problem to define the contents and borders of the concept of national security. In the context of legal vagueness of the concept, author of the article approach to the relation between public education and national security through the prism of various threats. The existing threats cause unsafety of the state, influence and also allow to define the contents of national security. It help to define the place of public education in entire security system as well. Public education should be understood as an issue of internal social life of the state and not an object of national security, because the urge for it derives from inside of the state, not from outside. Altogether we should consider that inside and outside threats are well related. It is a common case when internal threats of some state become also an external threats for other countries. The lack of resources urge weaker countries to seek security by reducing inside threats, but not directly outside ones. Considering interrelations of various threats it could be concluded that public education is inseparable and specific part of national security, as well as a unique indicator of state’s strength and its internal organization. We offer to include concepts of social culture and education into the legal definition of national security.